Managing pre-eclampsia and eclampsia in Dar es Salaam public health facilities: A focus on equipment, supplies, drugs and knowledge of healthcare workers (Tanzania Medical Journal, 2017)
IntroductionSevere pre-eclampsia and eclampsia (PE/E) is associated with high maternal and neonatal morbidity and mortality. Early detection and treatment of pre-eclampsia may prevent progression to severe PE/E. When severe PE/E occurs, timely use of anticonvulsants and antihypertensives (as part of emergency obstetric and neonatal care) are needed to reduce morbidity and mortality. This study is aimed at assessing the capacity in managing PE/E in public health facilities in Dar-es-Salaam, Tanzania.MethodsA descriptive cross-sectional study was conducted in selected public health facilities in Dar-es-Salaam city that offer reproductive and child services. The health facilities included four hospitals, three health centres and 23 dispensaries. A checklist was used to assess availability of equipment, supplies and drugs, and a structured questionnaire administered by an interviewer was used to assess healthcare workers’ knowledge on risks, symptoms, and drugs used to manage for PE/E. The results are presented as proportions.ResultsGuidelines for management of PE/E were available in all hospitals and health centres while 39% of the dispensaries had no the guidelines. Functioning blood pressure machines and stethoscopes were available in all facilities but urine test strips for detecting protein in the urine were available in only one hospital (25%) and 9 (39%) dispensaries. Anticonvulsant drugs were available in all health facilities. Magnesium sulphate, the first-line recommended anticonvulsant, was available in only a quarter of the dispensaries. A quarter of the dispensaries had nifedipine or methyldopa available as antihypertensives, with availability for both drugs being 75% and 100% in the hospitals and health centres respectively. The antihypertensive hydralazine was available in 50%, 33% and 8% of the hospitals, health centres and dispensaries respectively. Calcium gluconate was available in one hospital and one health centre only.Healthcare workers were knowledgeable regarding most risk factors, symptoms and drugs for treatment of hypertension and convulsions in PE/E. A higher proportion of doctors were knowledgeable of the risk factors, symptoms and drugs than the nurses and clinical officers. The majority of the healthcare workers mentioned magnesium sulphate as the drug for treatment of convulsions in PE/E.ConclusionsThere is insufficient screening and management of PE/E due to lack of equipment, supplies and drugs. Healthcare workers are relatively knowledgeable regarding risk factors, symptoms and drugs for managing PE/E. This calls for an increase in availability of equipment, supplies and drugs for managing women with PE/E. Healthcare workers need to receive ongoing education to sustain quality care for women with PE/E.